Peranan Hukum Islam dalam Proses Pembelajaran dan Pengembangan Karakter Siswa - Irawati, Sri Ayu (Ideas Publishing, 2024)
Education shapes human character, Islamic law plays an important role in the learning process and personality development of students. The research problem is the role of Islamic law in education and what students' attitudes towards Islamic law are. The aim of the research is to examine the role of Islamic law in shaping student character. The research method uses a literature review method. In-depth review of relevant literature, including Islamic education theory. Research results play an important role in the learning process and student personality development. Through Islamic education, we can create a learning environment that prioritizes honesty, morality and independence and creates people who contribute to society.